STUDI EMPIRIS MENGENAL PENERAPAN METODE SAMPLING AUDIT DAN FAKTOR – FAKTOR YANG MEMPENGARUHI PENGGUNAAN METODE SAMPLING AUDIT OLEH AUDITOR BANK INDONESIA SEMARANG - - Khanifah (AKSES: Jurnal Ekonomi dan Bisnis, 2009)
To obtain the adequate evidence, auditor doesn ‘t have to test all existing transaction. Along of cost benefit consideration, it is impossible for auditor to test all evidence. Based on this consideration : then in profession recognized widely that most evidence obtained using sampling. The limited audit sampling research motivated the writer to conduct this research. Researcher take the Indonesian bank auditor as research subject because sampling problems in government audit differ from the practice make an audit of the private sector. The purpose of this research is portraying how sampling audit practice in Indonesian Bank and explore factors affecting the use of sampling method by Indonesian Bank auditors. The responses from 30 respondents show 36,67 % respondents did not use the statistical sampling method. In non – statistics sample selection method, two techniques which less  get the support empirically namely block and systematic sampling, in the third (20,45%) and fourth rank ( 15,91%). There is indication of selection bias mostly in size, measure and location. Most respondents (80%) answered that they did not get formal training in avoiding selection bias. But that way only 43,33 % respondents replied they did not use the procedures to mitigate the selection bias. There are four factors which hyphotesized affecting the methode used in audit sampling. These factors are auditor perception to statistical sampling method, auditor perception to perceived audit risk, time pressure and internal control system. Result from logit regression test indicated that among four factors hyphotized, no one sigficantly influent to the methode used in audit sampling.Keyword : Audit sampling, Indonesian Bank Auditor.